2015
DOI: 10.1002/advs.201500205
|View full text |Cite
|
Sign up to set email alerts
|

Fe@N‐Graphene Nanoplatelet‐Embedded Carbon Nanofibers as Efficient Electrocatalysts for Oxygen Reduction Reaction

Abstract: An activated carbon nanofiber (CNF) is prepared with incorporated Fe‐N‐doped graphene nanoplatelets (Fe@NGnPs), via a novel and simple synthesis approach. The activated CNF–Fe@NGnP catalysts exhibit substantially improved activity for the oxygen reduction reaction compared to those of commercial carbon blacks and Pt/carbon catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…A novel nitrogen-doped-graphene nanoplatelets of Fe@N-graphene nanoplatelet-embedded carbon nanofibers was proposed by Ju et al [94], delivering half-wave potential value 0.8 V vs. RHE (Figure 6), which is the same as Pt. Its high activity was due to the high number of functional groups.…”
Section: Dual Hetero-atom Doped Electrocatalystsmentioning
confidence: 99%
“…A novel nitrogen-doped-graphene nanoplatelets of Fe@N-graphene nanoplatelet-embedded carbon nanofibers was proposed by Ju et al [94], delivering half-wave potential value 0.8 V vs. RHE (Figure 6), which is the same as Pt. Its high activity was due to the high number of functional groups.…”
Section: Dual Hetero-atom Doped Electrocatalystsmentioning
confidence: 99%
“…[5][6][7][8][9][10] The cathodic oxygen reduction reaction (ORR) is a critical process in fuel cells and largely decides their ultimate performance. [11][12][13][14] Although platinum (Pt) and platinum-based alloys are the best known ORR catalysts, the scarcity and declining activity of Pt-based catalysts significantly impede their practical use. 15 Therefore, the development of electrocatalysts with low price, high-efficiency and high stability as an alternative to Pt for the ORR is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…graphene structures have been suggested as promising catalyst supports. [24,25] In electrocatalysts with MÀNÀC functionalized group, two crucial factors govern the enhanced ORR activities, i. e., (i) the elemental composition and the interaction between different components, which determine the intrinsic nature of active site; and (ii) interplanar spacing of the neighboring graphene sheets allowing both sides of each graphene sheet to be accessible to the ORR-relevant species (H + , O 2 , H 2 O). [23] Recently, several research groups have reported that transition metal (Fe, Co) substitution in the nitrogen-doped carbon-based material (MÀNÀC) could improve ORR activities.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Recently, several research groups have reported that transition metal (Fe, Co) substitution in the nitrogen-doped carbon-based material (MÀNÀC) could improve ORR activities. FeÀNÀC functional groups in this graphene nanoplatelets (GnPs) offering the additional catalytic active sites for ORR can lower the amount of Pt while maintaining ORR performance [25] . [24,26] In these regards, we designed a new catalyst by anchoring low amount of Pt on the substrate of iron (Fe) and nitrogen (N) co-doped graphene nanoplatelets (FeNÀGnPs).…”
Section: Introductionmentioning
confidence: 99%